THE SOYBEAN (Glycine max L) GENETIC PARAMETERS OBTAINED BY A SINGLE CROSSING THREE VARIETIES ON F2 GENERATION - Tioner Purba; Arvita Netti Sihaloho; Wahyunita Sitinjak (Agros Journal of Agriculture Science, 2023)
This study was conducted to determine the genetic parameters and selective traits of soybean that can be used in the single crossing of three different female parental varieties with the same male parent. Furthermore, this study was conducted between September and November 2020 on the Raya Usang agricultural land, which was located at the Dolog Masagal in Simalungun District with an altitude of 1,090 m above sea level. An augmented design was used in this study, which involved the crossing of three F2 lines, as well as the four parents. The plot size had a dimension of 10mx50m, with a spacing of 20cmx30cm. There were about 200 F2 seedlings and four elders containing 100 plants each, which were fertilized and maintained as needed. The data collected on each individual plant were analysed to determine the genetic diversity, coefficient of genetic, genetic progress, the predictive value of broad meaning heritability, and the correlation between the observed characters. The character selection was determined using about twenty genotypes from the F2 generation depending on the increase in heritability and KGH values, as well as the significant correlation between characters.. The results showed the value of heritability and expected genetic progress (EGP) F2 (Grobokan x Tanggamus, Anjasmoro x Tanggamus and Argomulyo x Tanggamus) was high while phenotypic correlation of quantitative characters of  generation F2 (Grobokan x Tanggamus, Anjasmoro x Tanggamus and Argomulyo x Tanggamus) to all the characters observed has a real and high positive value. Key words: cross, genetic, heritability, varieties